Penerapan Metode Pieces Dalam Analisis Kinerja Website Lindungi Hutan - Darmansah Darmansah; Yeyi Gusla Nengsih (STMIK Budi Darma, 2022)
Protect the Forest website is a platform that is used to raise funds for forest conservation. This platform focuses on planting activities as an effort to conserve the environment and the welfare of seed farmers. The Protect the Forest website is an important part of the Protect the Forest business process, so the performance of the website must be analyzed. Analysis is used to determine the success of websites and related businesses in order to optimize these websites to provide a better user experience. This study applies the PIECES method which includes aspects of performance, information, economics, control, efficiency and service. This method serves to measure whether or not an aspect of an information system is good or bad. Then in data collection using a questionnaire and a Likert scale. In measuring the performance aspect, this research also uses the online tools PageSpeed Insights and GTmetrix. From the analysis results obtained in this study, it is known that the performance aspect of the Protect Forest website is in good category, information aspect is in good category, economy aspect is in very good category, control aspect is in good category, the efficiency aspect is classified as good category and the service aspect is in good category with an average value of 85%.